Exploration vs exploitation, impulse balance equilibrium, and a specification test for the El Farol bar problem - Alan P. Kirman; François Laisney; Paul Pezanis-Christou (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
The paper reports on market-entry experiments that manipulate both payoff structures and payoff levels to assess two stationary models of behaviour: Exploration vs Exploitation (EvE, which is equivalent to Quantal Response Equilibrium) and Impulse Balance Equilibrium (IBE). These models explain the data equally well in terms of goodness-of-fit whenever the observed probability of entry is less than the symmetric Nash equilibrium prediction; otherwise IBE marginally outperforms EvE. When assuming agents playing symmetric strategies, and estimating the models with session data, IBE yields more theory-consistent estimates than EvE, no matter the payoff structure or level. However, the opposite occurs when the symmetry assumption is relaxed. The conduct of a specification test rejects the validity of the restrictions on entry probabilities imposed by EvE for agents with symmetric strategies, in 50 to 75% of sessions and it always rejects it in the case of IBE, which indicates that the symmetric variant of these models has little empirical support.
Keywords: C7; C92; 330; congestion games; exploration vs exploitation; quantal response equilibrium; impulse balance equilibrium; specification test; experimental economics